Correlation between alveolar bone morphology and volumetric dimensional changes in immediate maxillary implant placement: A 1‐year prospective cohort study. Issue 9 (23rd June 2020) - Borges, Tiago; Fernandes, Danilo; Almeida, Bruno; Pereira, Miguel; Martins, David; Azevedo, Luís; Marques, Tiago
Abstract: Background: After a single tooth extraction, remodelling processes are initiated and morphological changes occur in the alveolar bone. It has been suggested that implant placement in a fresh extraction socket may partly reduce the alveolar ridge contraction and that several factors like the thickness of the buccal bone wall and the size of the gap between the implant and the facial bone wall may play a role on peri‐implant tissues dimensional alterations. Methods: Twenty‐six patients treated with single‐tooth maxillary implants were included in this study. A CBCT exam allowed to access the initial buccal bone thickness (BT). Digital impressions were taken prior to extractions (T0), 1 month (T1), 4 months (T2), and 12 months (T3) after implant insertion and superimposed with a computer software allowing to quantitatively analyse the three‐dimensional changes occurred in the adjacent tissues. Variables related to thickness and volume were computed. Results: Participants with BT ≤ 1 mm exhibited a significantly increased buccal peri‐implant tissue thickness change than patients with BT > 1 mm ( P = 0.049). At T3 patients representing BT ≤ 1 mm exhibited a total volume change of −8.53% ± 5.47% compared with patients presenting BT > 1 mm, −4.37% ± 2.08%. No statistical significance was found on the distance between implant shoulder and the buccal bone plate (BID) effect. Conclusion: After the first year of treatment peri‐implant tissues showed continuous changes resulting in a higher thickness and volume reduction at thin buccal bone plates.